2014
DOI: 10.3233/bme-141217
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of the transcriptome and targetome identifies the regulatory network of miR-16: An inhibitory role against the activation of hepatic stellate cells

Abstract: Hepatic stellate cell (HSC) activation is the critical event of liver fibrosis. Abnormality of miR-16 expression induces their activation. However, the action model of miR-16 remains to be elucidated because of its multiple-targeted manner.Here, we report that miR-16 restoration exerted a wide-range impact on transcriptome (2,082 differentially expressed transcripts) of activated HSCs. Integrative analysis of both targetome (1,195 targets) and transcriptome uncovered the miR-16 regulatory network based upon bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Studies showed that miR-16 targets the 3′ UTR of vascular endothelial growth factor (VEGF) to regulate angiogenesis [35, 36]. In addition to bcl-2 and VEGF, TGF-β, PI3K-Akt and p53 are considered to be the potential targets of miR-16 [37]. In this study, we identified β 2 -AR as a direct target gene of miR-16, and did not investigate other potential targets.…”
Section: Discussionmentioning
confidence: 94%
“…Studies showed that miR-16 targets the 3′ UTR of vascular endothelial growth factor (VEGF) to regulate angiogenesis [35, 36]. In addition to bcl-2 and VEGF, TGF-β, PI3K-Akt and p53 are considered to be the potential targets of miR-16 [37]. In this study, we identified β 2 -AR as a direct target gene of miR-16, and did not investigate other potential targets.…”
Section: Discussionmentioning
confidence: 94%
“…However, one study reports that forced miR-16 expression suppressed the activation of HSCs, which is the critical event in liver fibrogenesis, likely through negative cell-cycle regulation, enhanced fibrolysis, and increased apoptosis. 283 Subsequent integrative analysis identified the regulatory network of miR-16…”
Section: Ppp2r1amentioning
confidence: 99%
“…and found that PPP2R1A is a target of miR-16 and that PP2R1A constitutes a key regulatory network node that mediates the miR-16 action in proliferation, ECM deposition, and survival. 283 Interestingly, treatment of endometriotic cells with peritoneal fluid from women with endometriosis reduced the expression of miR-16. 284,285 Thus, there is a possibility that miR-16 downregulation may induce PPP2R1A activation, facilitating the progression of fibrogenesis in endometriosis.…”
Section: Ppp2r1amentioning
confidence: 99%
“…19 However, our team found that there was a decrease in miR-16 level with the activation of hepatic stellate cells (HSCs), while its upregulation increased apoptosis and inhibited the activation of HSCs and finally, reduced hepatic fibrosis. 39,40 Other miRNAs miR-197 and miR-99 levels in VAT samples are significantly correlated with pericellular fibrosis in NASH patients. 41 Other studies have confirmed that the levels of miR-150, miR-182, miR-183, miR-224 and miR-31 are increased, while those of miR-17, miR-219a, miR-378i and miR-590 are decreased in liver biopsy specimens of patients with severe fibrosis or cirrhosis (F3-F4) compared to individuals without fibrosis (F0).…”
Section: Mir-16mentioning
confidence: 99%
“…Increased miR-16 expression induces the apoptosis of HSCs and inhibits their activation, and thus improves liver fibrosis. 39,40 MiR-182 expressions are decreased in fibrotic samples of the liver, and FOXO3 is identified as its potential target gene. 42 Hepatic miR-146a is the most significantly downregulated miRNA in mice with NASH induced by MCD diet.…”
Section: Mirnas In Hepatic Inflammation and Fibrosismentioning
confidence: 99%